Factors Affecting Financial Performance of Culinary Entrepreneuers - O’nelysia Marthing; Carunia Mulya Firdausy (Yayasan Riset dan Pengembangan Intelektual, 2023)
The rise of people who become entrepreneurs currently makes it difficult to maintain financial performance in the culinary business sector. This study aims to determine the effect of Entrepreneur Orientation, and Opportunity Exploitability on the Financial Performance of Culinary Entrepreneurs in Jabodetabek with Innovation Capability and Flexibility Strategy as Mediating Variables. The subject of this study was culinary entrepreneurs in the Jakarta, Bogor, Depok, and Bekasi (Jabodetabek) areas. The method to collect the data was by distributing questionnaires to 200 respondents. This study used a quantitative PLS-SEM analysis. The results of this study indicate that Opportunity Exploitability has a positive and significant effect on Financial Performance. Opportunity Exploitability has a positive and significant impact on Strategy Flexibility. Strategy Flexibility has a positive and significant effect on Financial Performance. The Flexibility Strategy mediates the Exploitation of Opportunities on Financial Performance. Entrepreneurial orientation has a positive and significant effect on financial performance. Entrepreneurial orientation has a positive and significant effect on Innovation Capability. Innovation Capability has a significant positive effect on Financial Performance. Innovation Capability Mediates Entrepreneurial Orientation on Financial Performance.